2017
DOI: 10.1093/jxb/erx048
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of the 3D cell shape changes driving soybean germination

Abstract: HighlightChanges in 3D anisotropy across the soybean axis during seed germination revealed a radicle-biased pattern of cell growth and position-specific changes in cell anisotropy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 22 publications
0
7
0
1
Order By: Relevance
“…This control takes place mainly in cortical cell layers of the upper embryonic axis, suggesting a tissue-specificity and partially overlapping roles of homeodomain genes [59,60]. Many morphological features related to elongation events and cell wall remodeling in the embryo seem to be conserved between species [375][376][377]. Moreover, the epidermal HD-ZIP-DELLA-L1 box regulatory module was found to be conserved in cotton where it controls fiber cell elongation [378], indicating that it has been recruited by other developmental stages.…”
Section: Regulation Of Germination From a Spatial And Mechanical Persmentioning
confidence: 99%
“…This control takes place mainly in cortical cell layers of the upper embryonic axis, suggesting a tissue-specificity and partially overlapping roles of homeodomain genes [59,60]. Many morphological features related to elongation events and cell wall remodeling in the embryo seem to be conserved between species [375][376][377]. Moreover, the epidermal HD-ZIP-DELLA-L1 box regulatory module was found to be conserved in cotton where it controls fiber cell elongation [378], indicating that it has been recruited by other developmental stages.…”
Section: Regulation Of Germination From a Spatial And Mechanical Persmentioning
confidence: 99%
“…For example, several groups of genes have been related to germination sensu stricto (the first stage of the germination process), mainly those involved with DNA repair, such as oxidative stress defense, cell respiration and hydrolysis of reserves, and cell elongation and expansion [ 13 , 14 , 15 , 16 , 17 ]. At the same time, the synchrony between the processes promotes a chain reaction that culminates in the growth of the embryonic axis, which leads to the occurrence of visible germination, i.e., growth of the new individual from the embryo, through the protrusion of the radicle due to the elongation of the transition zone between the hypocotyl and the radicle [ 18 ] as occurring in soybean embryos [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…In line with this, recent elegant works in A. thaliana showed that GA gradients correlate with cell length in dark-grown hypocotyls 36,37 . We hypothesize that this might be the case in soybean embryonic axes, particularly in the context of the recently described radicle-derived growth pattern in germinating soybean embryos 38 .
Figure 3Hormone biosynthesis pathways. Some GA deactivation and signaling genes discussed are also included.
…”
Section: Resultsmentioning
confidence: 86%
“…Collectively, these results show that GA modulates different genes involved in ABA biosynthesis, signaling and transport, which might directly interfere with GA:ABA gradients along germinating soybean embryonic axes. This GA:ABA dynamics might be involved in the differential cell expansion patterns observed in germinating soybean embryos 38 .
Figure 4Hormone signal transduction. Rectangles with red lines represent gene families with at least one DEG.
…”
Section: Resultsmentioning
confidence: 98%